An audit of pattern and cost of medication used in diabetes and hypertension patients in Hospital Raja Perempuan Zainab II - Rusli, Norefin; Che Ku Mamat, Maryam Jamilah (2010)
This project is an audit on pattern of medications use to treat diabetes and hypertension. Through this project, we can know the most prescribed medicines to treat both health problems. We focused our study at the Satellite Pharmacy by collecting the discharged prescriptions from medical wards. However, we only chose prescriptions that have diagnosis of both diabetes and hypertension. We analyzed all the data by using Microsoft Excel. We also compared the result that we have with the Ministry of Health guidelines. Through this study, Gliclazide (32%) has become the number one most prescribed medicines to treat diabetes followed by Metforrnin (29%). However, the Ministry of Health guidelines indicated that Metforrnin should be the first line therapy to treat diabetes and should be the most prescribed antidiabetic medicine. The cost spent for all antidiabetics involved was RM 1266.01 in six month time. In hypertension cases, Amlodipine (22%) is the number one most prescribed medicine to treat this health problem followed by Metoprolol (17%). However, the local Clinical Practice Guideline (CPG) on hypertension recommends beta-blockers or diuretics as drugs of first choice for control of uncomplicated hypertension. The cost spent for all antihypertensive involved was RM 3687.80 in six month time.